Clinical profile and radiological evaluation of severe pneumonia in children, age 2 months up to 5 years: a descriptive cross-sectional study - Islam Khan, Mohammad Monirul; Hoque, Mohammad Azizul; Begum, Bilkis; Islam, Mohammad Didarul (Community Based Medical Journal, 2018)
Acute respiratory illness, primarily pneumonia, is the main cause of mortality in children under five years in most developing countries - result in 1.9 million deaths each year. To reduce mortality from these diseases, WHO introduced case management guidelines based on simple clinical signs for diagnosing pneumonia followed by empirical treatment with antibiotics. For management purposes, pneumonia is subclassified according to its severity by using general danger sign, chest indrawing or fast breathing. But these factors are influenced by malaria, meningitis, hyperactive airway disorder, bronchiolitis and fever. So clinical profile and their chest radiographs were analyzed in children aged 2-59 months who presented to a health facility with severe pneumonia using WHO guidelines. The purpose was to observe the clinical profile, evaluate radiological features of severe pneumonia and also to correlate the efficacy of clinical criteria with that of radiological findings. The study was conducted under the department of Pediatrics, Mymensingh Medical College Hospital and the samples were collected from the Inpatient department of Pediatrics in this hospital. It was a cross sectional observational study. 100 consecutive samples were collected from mothers with their children aged 2-59 months who met the inclusion criteria. Out of 100 children 56 were male and 44 were female children and male female ratio was 1.3:1. Majority (66%) of the children were partially immunized, 37% children were fully immunized and only 7% children were unimmunized as per EPI schedule. 42% of the children were malnourished and 13% were severely malnourished. Regarding clinical presentation all the patients presented with fever with cough (100%), 88% with difficult breathing, 11% had wheeze and 25% presented with general danger signs. Among the physical signs' temperature raised in 92%, Chest indrawing in 88%, flaring of alaenasi 78%, central cyanosis in 15%, pallor in 28%, stridor in 3%, bulged fontanel in 2% cases and BCG scar present in 65% of the cases. Clinical diagnosis of the studied cases revealed bronchiolitis in 31%, lobar pneumonia in 23%, bronchopneumonia in 27%, asthma in 12% and pulmonary tuberculosis in 7% cases. Routine examination of blood revealed 70% children were mild to moderately pale, 63% leukocytosis, 52% neutrophilic leukocytosis, 15% lymphocytic leukocytosis, ESR was raised in 52% of cases. Chest X-ray showed normal skiagram in 36%, consolidation in 23%, bronchopneumonia in 16%, nonspecific infection in 17% and hilar lymphadenopathy in 7% cases. 12% patients responded with ampicillin alone, 30% required gentamicin in addition, 39% required cloxacillin in addition to ampicillin and gentamicin, only ceftriaxone in 12% and 7% cases required anti tubercular treatment. Steroid used in 30% cases and bronchodilator in 42% cases. Immediate hospital outcome of these patients showed 78% cases improved, 12% patients left hospital against medical advice and 8% patients died in the hospital. CBMJ 2018 July: Vol. 07 No. 02 P: 24-33